Audiology follow-up reveals a high incidence of hearing impairment in patients with congenital hypothyroidism. (4th April 2011) - Prentice, P; Raine, J; Sirimanna, T; Langham, S; Rajput, K; Peters, C; Dattani, M
Abstract : Introduction: Animal studies demonstrate the importance of thyroxine in normal auditory development. Human reports show associations between congenital hypothyroidism (CH) and hearing loss (HL). However, most reports are small and pre-date national hypothyroid screening. There are no reports since the introduction of the national newborn hearing screen (NNHS), nor national guidelines on appropriate audiology follow-up. Aim: To evaluate the incidence and type of HL, and review audiological follow-up, in a cohort of young children with CH, who underwent NNHS. Method: A retrospective case note review of babies seen by an endocrinology centre (January 2006–December 2008), with CH (Thyroid stimulating hormone ≥20 μ/l). Demographic, endocrine and audiological data were collected. Results: 102 babies were included: 41% male, 50% white, 34% Asian, 6% Mixed, 6% Other, 2% Black, 2% Not-specified, with 14% consanguinity, and a mean gestational age of 39.3 weeks. A large proportion had sublingual thyroid glands (40%) or dyshormonogenesis (25%). Levothyroxine treatment was started at 12.2+/−6.6 days, at a dose of 7.9 mcg/kg/day+/−1.9. Of 85 infants seen by audiology (83%), at 50.7+/−25.3 days, 81 had auditory brainstem responses, 7 bone conduction, 74 tympanometry, 34 otoacoustic emissions. No babies had severe/profound HL. 30 (35%) had mild-moderate HL (11 babies had moderate HL (40–69 dbnHL, European Working Group classification)). Half of those with moderate HL had sensorineural HL. This subgroup had a higher proportion of thyroid agenesis (55% vs 27% in normal hearing group). NNHS results for these children were: 4 normal, 3 not finished, 3 not finished with abnormal results, 1 abnormal. Conclusions: Over 80% of CH patients were seen by audiology. 35% had mild-moderate HL, suggesting a high risk of hearing problems, even with early thyroxine replacement. Approximately half had conductive HL. No infant had severe HL. However, these data should be cautiously interpreted in this relatively small cohort. Our preliminary findings underline the importance of audiology follow-up, since initial NNHS may not pick up significant HL. Although retrospective, with no controls, this study emphasises the need for a prospective long term study. This will allow detailed evaluation of the natural history of HL in CH, enabling appropriate audiological care and information for families.